Properties and use of the Dermatology Life Quality Index in Patients with Psoriasis - D. A. Andreev; N. N. Kamynina (Здоровье мегаполиса)
Introduction. Based on the results of clinical studies, considerable experience for the Dermatology Life Quality Index (DLQI) has been accumulated worldwide. The Index can be integrated into the routine management of patients with psoriasis. The purpose of the study was to systematically analyze exclusively recent data (from the last five years) on the use of the DLQI in the assessment of psoriasis severity.Materials and methods. An extensive search for relevant sources was carried out using the PubMed/Medline bibliographic database. The search string used the keywords Dermatology Life Quality Index, Psoriasis. Works not mainly related to the DLQI usage as well as similar publications describing repeated properties and characteristics of the DLQI were excluded.Results. The DLQI can be used in both clinical research and data analysis in clinical practice. The DLQI has been used in a number of studies to assess the effectiveness of novel types of therapy. The DLQI indicators usually correlate with the questionnaire results obtained from the Psoriasis Area and Severity Index (PASI) and the results of other quality-of-life scales. Most of the scientific publications discuss the use of the DLQI in clinical trials, including the analysis of the effectiveness of biological therapy.Discussion. To obtain all the evidence concerning the applicability of the DLQI and its modifications in various clinical situations, an integrated approach based on the combination of various scales in pilot studies could be expanded.